P648 Clinical feasibility of dried blood sampling for infliximab in IBD patients. (16th January 2018) - Berends, S; D'Haens, G; Bloem, K; Schaap, J; De Vries, A; Rispens, T; Mathôt, R
Abstract: Background: Therapeutic drug monitoring (TDM) is important to optimise outcome of infliximab (IFX) treatment in inflammatory bowel disease (IBD). Dried blood spot (DBS) sampling using capillary blood obtained via a finger prick could facilitate TDM, since patients can administer this finger prick themselves at any time and away from the hospital. We investigated the predictive performance and the feasibility of DBS for measuring IFX concentrations in IBD patients. Methods: We studied 40 adult IBD patients receiving IFX therapy according to standard guidelines. From each patient blood was obtained simultaneously via venepuncture and DBS via finger prick by a trained employee at 3 different time points (trough, peak, 3–5 weeks after infusion). One week before IFX infusion (time point 4), patients performed DBS at home and the sample was directly sent to Sanquin laboratories, Amsterdam, The Netherlands. The corresponding serum concentration for this time point was estimated using Bayesian pharmacokinetic analysis using the three samples obtained by venepuncture. Capillary blood was obtained by a microsampling device developed by Neoteryx™. Haematocrit (Hct) values of each individual patient were used to convert DBS eluate results to values which can be compared with (venous) serum concentrations. Spearman's correlation coefficient was used to assess correlation and bias was calculated. Results: Forty IBD patients were included with median [interquartile range] age: 41 [32–50], albumin: 43 mg/l [41–45], and CRP: 1.3 mg/l [0.4–4.4]. IFX concentrations obtained from the DBS method correlated strongly with serum results from the same patient for IFX trough- and mid-interval concentrations (Spearman correlation coefficient >0.88) and moderately for IFX peak concentrations (Spearman correlation coefficient = 0.69). IFX serum concentrations from the DBS performed at home showed strong correlation with the concentrations obtained by Bayesian analysis (Spearman correlation coefficient = 0.71). No structural bias was shown (Table 1). Conclusions: DBS via finger prick can be used for the assessment of serum IFX concentrations. More importantly, we showed the feasibility of using DBS via finger prick at home. This method greatly facilitates the use of TDM in the treatment of IBD patients using IFX.